The emerging threat of pre-extensively drug-resistant tuberculosis in West Africa: preparing for large-scale tuberculosis research and drug resistance surveillance. Issue 1 (December 2016) - Gehre, Florian; Otu, Jacob; Kendall, Lindsay; Forson, Audrey; Kwara, Awewura; Kudzawu, Samuel; Kehinde, Aderemi; Adebiyi, Oludele; Salako, Kayode; Baldeh, Ignatius; Jallow, Aisha; Jallow, Mamadou; et al.
Abstract Background Drug-resistant tuberculosis (TB) is a global public health problem. Adequate management requires baseline drug-resistance prevalence data. In West Africa, due to a poor laboratory infrastructure and inadequate capacity, such data are scarce. Therefore, the true extent of drug-resistant TB was hitherto undetermined. In 2008, a new research network, the West African Network of Excellence for Tuberculosis, AIDS and Malaria (WANETAM), was founded, comprising nine study sites from eight West African countries (Burkina Faso, The Gambia, Ghana, Guinea-Bissau, Mali, Nigeria, Senegal and Togo). The goal was to establish Good Clinical Laboratory Practice (GCLP) principles and build capacity in standardised smear microscopy and mycobacterial culture across partnering laboratories to generate the first comprehensive West African drug-resistance data. Methods Following GCLP and laboratory training sessions, TB isolates were collected at sentinel referral sites between 2009–2013 and tested for first- and second-line drug resistance. Results From the analysis of 974 isolates, an unexpectedly high prevalence of multi-drug-resistant (MDR) strains was found in new (6 %) and retreatment patients (35 %) across all sentinel sites, with the highest prevalence amongst retreatment patients in Bamako, Mali (59 %) and the two Nigerian sites in Ibadan and Lagos (39 % and 66 %). In Lagos, MDR is already spreading actively amongst 32 % of new patients. Pre-extensively drug-resistant (pre-XDR) isolates are present in all sites, with Ghana showing the highest proportion (35 % of MDR). In Ghana and Togo, pre-XDR isolates are circulating amongst new patients. Conclusions West African drug-resistance prevalence poses a previously underestimated, yet serious public health threat, and our estimates obtained differ significantly from previous World Health Organisation (WHO) estimates. Therefore, our data are reshaping current concepts and are essential in informing WHO and public health strategists to implement urgently needed surveillance and control interventions in West Africa.